Successful smallpox eradication: what can we learn to control COVID-19? - Heymann, David L.; Wilder-Smith, Annelies (Journal of travel medicine, 2020)
On 8 May 2020, the World Health Organization (WHO) celebrated the land mark milestone of the declaration of smallpox eradication exactly 40 years ago. The declaration marked the end of a disease that had plagued humanity for at least 3000 years, killing an estimated 300 million people during the 20th century alone.1 As recently as 1967, the year in which eradication efforts were intensified, an estimated 2.7 million deaths were attributed to smallpox.Smallpox was eradicated thanks to a global effort that began in 1959 spearheaded by WHO, further intensified in 1967. It involved 10 000 of health workers around the world who administered an estimated half a billion vaccinations. The cost of the intensified effort, led by WHO, was estimated to be 300 million USD in cash by global donors in addition to countries contributions. Those investments were well spent as they now save the world far more than U
Gesehen am 17.02.2022